A high glucose concentration during early stages of in vitro equine embryo development alters expression of genes involved in glucose metabolism. (12th October 2020) - Sánchez‐Calabuig, María J.; Fernández‐González, Raúl; Hamdi, Meriem; Smits, Katrien; López‐Cardona, Angela P.; Serres, Consuelo; Macías‐García, Beatriz; Gutiérrez‐Adán, Alfonso
Abstract: Background: Equine embryos exhibit an unusual pattern of glucose tolerance in vitro and are currently cultured in hyperglycaemic conditions. Objective: Our main objective was to analyse the effect of different glucose concentrations on in vitro‐produced equine embryo development and quality. Study design: Experiments comparing in vitro and in vivo produced embryos. Methods: Oocytes (n = 641) were collected from post‐mortem ovaries, matured in vitro and fertilised by intracytoplasmic sperm injection (ICSI). Embryo culture was divided from Day 0 to Day 4 and from Day 4 to Day 9 in three groups: 5‐10 (5 and 10 mmol/L glucose respectively; n = 87); 5‐17 (5 and 17.5 mmol/L; n = 66); and 10‐17 (10 and 17.5 mmol/L; n = 117). A control group of 20 in vivo produced blastocysts was included. Cleavage and blastocyst rates were evaluated and embryos were snap‐frozen for analysis of the relative mRNA expression of genes related to mitochondrial function, DNA methylation, apoptosis, glucose transport and metabolism. Results: No differences were observed in the cleavage or blastocyst rates among in vitro groups. Under high glucose conditions in vitro (10‐17 group), BAX / BCL2 was higher, and PFKP, LDHA and COX2 were overexpressed compared to all other groups. The two groups with 5 mmol/L glucose concentration during the first culture stage (5‐10 and 5‐17) displayed similar patterns which differed to the 10‐17 group. Main limitations: Conclusions related to embryo quality are based on gene expression patterns. Transfer of in vitro‐produced embryos would reveal whether the observed differences improve embryo developmental competence. Conclusions: Five mM glucose during the first days of culture seems to be preferable to avoid over‐activation of embryonic glycolytic pathways. Further studies are necessary to determine whether this improves embryo developmental competence.